$η$-Ricci solitons in a LP-Sasakian manifolds admitting quarter-symmetric metric connection - Abhishek Singh; Sangeeta Gautam; Lalit Kumar (Ratio Mathematica, 2025)
The objective of this paper is to investigate the $η$-Ricci solitons in a LP-Sasakian manifolds admitting quarter-symmetric metric connection satisfying certain curvature conditions. We study the Ricci solitons in a LP-Sasakian manifolds admitting quarter-symmetric metric connection satisfying certain conditions. Finally, we have given an example of 3-dimensional $η$-Ricci solitons in a LP-Sasakian manifolds with respect to quarter-symmetric metric connection.